RANCANG BANGUN APLIKASI ABSENSI ONLINE PEGAWAI BERBASIS MOBILE ANDROID PADA SMK PGRI 2 KOTA JAMBI MENGGUNAKAN METODE WATERFALL: RANCANG BANGUN APLIKASI ABSENSI ONLINE PEGAWAI BERBASIS MOBILE ANDROID PADA SMK PGRI 2 KOTA JAMBI MENGGUNAKAN METODE WATERFALL - Sitorus, Doli Sumarlin (JUSS (Jurnal Sains dan Sistem Informasi), 2023)
In the system used, the employee attendance system at SMK PGRI 2 Jambi City is still manual, namely using paper media and a list of names and signatures. The manual system can be seen starting from the data collection and calculation of the number of attendance, the number of absences, to the calculation of the number of hours late for employees. Good, fast and efficient attendance data processing, by creating an Android Mobile-Based Employee Online Attendance Application at SMK PGRI 2 Jambi City. Where this application is expected to increase employee discipline, as well as facilitate the processing of employee attendance data, the author uses the Waterfall method in developing this software. employee himself. For testing the application, the author made several questions to teachers at SMK PGRI 2 Jambi City in the form of a questionnaire. As expected the authors of the respondents, totaling 20 people with details of 35% male and 65% female, generally welcomed the implementation of this application.